Qualitative and Quantitative Pcr Methods For Detection of Foods Containing Genetically Modified Soybean and Corn. - Abdullah, Tosiah (2006)
Genetically modified organisms (GMOs) can be defined as organisms in which their genetic materials have been altered in the ways that does not occur naturally by mating or natural combination. Polymerase chain reaction (PCR) method is used to detect genetically modified events in foods. The specific objectives of this study are to establish a sensitive, robust and rapid method for the detection of genetically modified events by using PCR and to conduct a preliminary survey for distribution of foods derived from genetically modified events in Malaysia. The two critical factors that were taken into account to achieve these objectives are the applicability of different DNA extraction methods for each kind of samples and PCR amplification conditions. Three different DNA extraction methods have been tested on soy, corn, potato and tofu (as a processed food).The DNeasy method as in a widely used commercial kit, Wizard method (Hemmer, 1997) and Cetyl-trimethyl ammonium bromide (CTAB) method (Jankiewicz et al., 1999) were evaluated in this study. The yield and purity of DNA were examined and compared. Quantification was accomplished by measuring UV absorbance at 260 nm and the suitability of DNA for PCR was tested. The results showed that there are sigruficant differences between the methods used. CTAB, Wizard and DNeasy methods produced DNA with ratio of A260/A280 range from 1.2 to 1.6, 1.9 to 2.2 and 1.7 to 1.9, respectively. However, the DNeasy method gave the optimum yield of DNA of high purity and was less time consuming. The primer pairs used for confirmation of the endogenous genes in the respective samples (Lectinl / Lectin6 for lectin gene in soya, Zein n-3' / Zein n-5' for zein gene in maize and PssOl n5'/PssOl n-3' for patatain gene in potato) produced the expected size of 318, 157 and 216 base pair, respectively. The results of this study showed that 18 out of 85 soy samples were contaminated by at least one of three introduced genetic elements consisting 35s promoter, Nopaline Synthase terminator and the structural gene of 5- enolpyruvylshikimate-3-phpsphate-synthas. Quantitative analysis of the 18 positive genetically modified soy samples showed that, seven samples contains 0.1 - 0.5% Roundup Ready Soy, four samples contains 0.5 - 1.0% Roundup Ready Soy and seven of them contains 1.0 - 2.0% Roundup Ready Soy.In contrast, none of the 52 was positive with these assays. Therefore they were categorized as non-GM products. These results revealed that PCR amplification method provides the key advantages of high sensitivity, robust and rapid operation whilst providing the requisites of careful experimental design that avoids both false-negative and/or false-positive results. Seven primer pairs (LECl/LEC6; Zein n- 3'/ Zein n-5'; PssOl n-5'/ PssOl n-3'; P35S 1-5'/ P35S 2-3'; HA-NOSll8-F/ HANOSllaR, Cryl(Al)/Cryl(M) and RRO1/ RRO4) chosen in this study produced an expected size of 318, 157, 216,101, 118, 107 and 356 base pair, respectively, fulfilling the product-size requirement and completed the whole detection procedure of GM events in food samples.